Decrease in Calcium Oxalate Levels in Porang Bulbs With Variations in Contact Time, Temperature and Volume of Averrhoa bilimbi Juice Solution: Penurunan Kadar Kalsium Oksalat Pada Umbi Porang Dengan Variasi Waktu Kontak, Suhu Dan Volume Larutan Sari Buah Belimbing Wuluh - Ratih Kusuma Wardani (Journal Pharmasci (Journal of Pharmacy and Science), 2022)
Porang tubers contain glucomannan which is widely used in industry. The high calcium oxalate contained in porang tubers is an obstacle in the use of porang tubers in the food industry. Organic acids such as citric acid can reduce calcium oxalate levels in porang tubers. Porang tubers cut with a thickness of 0.5 cm were immersed in a 7% solution of star fruit juice with variations in soaking time, temperature and volume of the soaking solution. Soaking porang tubers in 250 mL of star fruit juice solution at 60 °C for 15 minutes gave better results than soaking porang tubers at room temperature for 60 minutes. The lowest level of calcium oxalate was found in porang tubers that had been soaked in 7% starfruit solution for 15 minutes at 60 °C, which was 1.0873% (w/w).